Identification of Specific Gravity and Solubility in ethanol from citronella oil - Anwar Syahadat; Ayus Diningsih (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2022)
Introduction: Essential oil is also known as ethereal oil or flying oil (ethereal oil, volatile oil) produced by plants. The oil is volatile at room temperature without decomposition, has a bitter taste, smells good according to the smell of the plant that produces it, is generally soluble in organic solvents and insoluble in water. At high concentrations, essential oils can be used as local anesthetics, for example clove oil is used to treat toothaches, but can damage mucous membranes. Most essential oils also have strong antibacterial and antifungal properties. Methods: This research is a laboratory-based experimental study. Results: Based on the specific gravity test, the tested lemongrass oil has good quality because it meets the requirements of the Indonesian National Standard, namely the specific gravity must be in the range of 0.880 - 0.922. From the tests carried out twice (duplo) the results obtained were in that range with the value in the first Conclusion: The density of citronella oil is 0.8800 and the test sample meets the requirements of SNI. The solubility in ethanol of citronella oil is 1: 2 clear, the test sample meets the requirements of SNI.